Site Saturation Mutagenesis Applications on Candida methylica Formate Dehydrogenase - Gülşah P. Özgün; Emel B. Ordu; H. Esra Tütüncü; Emrah Yelboğa; Richard B. Sessions; Nevin Gül Karagüler (Scientifica)
In NADH regeneration, Candida methylica formate dehydrogenase (cmFDH) is a highly significant enzyme in pharmaceutical industry. In this work, site saturation mutagenesis (SSM) which is a combination of both rational design and directed evolution approaches is applied to alter the coenzyme specificity of NAD+-dependent cmFDH from NAD+ to NADP+ and increase its thermostability. For this aim, two separate libraries are constructed for screening a change in coenzyme specificity and an increase in thermostability. To alter the coenzyme specificity, in the coenzyme binding domain, positions at 195, 196, and 197 are subjected to two rounds of SSM and screening which enabled the identification of two double mutants D195S/Q197T and D195S/Y196L. These mutants increase the overall catalytic efficiency of NAD+ to 5.6×104-fold and 5×104-fold value, respectively. To increase the thermostability of cmFDH, the conserved residue at position 1 in the catalytic domain of cmFDH is subjected to SSM. The thermodynamic and kinetic results suggest that 8 mutations on the first residue can be tolerated. Among all mutants, M1L has the best residual activity after incubation at 60°C with 17%. These studies emphasize that SSM is an efficient method for creating “smarter libraries” for improving the properties of cmFDH.